2018
DOI: 10.1007/s00259-018-3985-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plasma glucose level on the pattern of brain FDG uptake and the predictive power of FDG PET in mild cognitive impairment

Abstract: Increasing BGL is associated with relative reduction of FDG uptake in the posterior cortex even in the "acceptable" range ≤ 160 mg/dl. The BGL-associated pattern is similar to the typical AD pattern, but not identical. BGL-associated variability of regional FDG uptake has no relevant impact on the power of FDG PET for prediction of MCI-to-ADD progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
2
13
0
2
Order By: Relevance
“…In our research, voxel-bases group comparison revealed hypometabolism in the region of the precuneus in the diabetic group compared to the obese. This could be in line with the results of Apostolova and co-authors who pointed out that elevated blood glucose level (98.4±15.8 mg/dl/5.5±0.88 mmol/L), even in the normal range (reference range 59–149 mg/dl/3.3-8.34 mmol/L) is associated with a decrease regarding [ 18 F]FDG uptake in the posterior cortex (Apostolova et al, 2018 ). Increasing plasma glucose levels causing reduced brain glucose metabolism in the region of the precuneus and the posterior cingulate gyrus detected by Ishibashi K and co-workers could also be in coherence with our result (Ishibashi et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…In our research, voxel-bases group comparison revealed hypometabolism in the region of the precuneus in the diabetic group compared to the obese. This could be in line with the results of Apostolova and co-authors who pointed out that elevated blood glucose level (98.4±15.8 mg/dl/5.5±0.88 mmol/L), even in the normal range (reference range 59–149 mg/dl/3.3-8.34 mmol/L) is associated with a decrease regarding [ 18 F]FDG uptake in the posterior cortex (Apostolova et al, 2018 ). Increasing plasma glucose levels causing reduced brain glucose metabolism in the region of the precuneus and the posterior cingulate gyrus detected by Ishibashi K and co-workers could also be in coherence with our result (Ishibashi et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…In our research, voxel-bases group comparison revealed hypometabolism in the region of the precuneus in the diabetic group compared to the obese. This could be in line with the results of Apostolova and coauthors who pointed out that elevated blood glucose level (98.4 ± 15.8 mg/dl/5,5 ± 0,88 mmol/L), even in the normal range (reference range 59-149 mg/dl/3,3-8,34 mmol/L) is associated with a decrease regarding [ 18 F]FDG uptake in the posterior cortex [30]. Increasing plasma glucose levels causing reduced brain glucose metabolism in the region of the precuneus and the posterior cingulate gyrus detected by Ishibashi K and co-workers could also be in coherence with our result [31].…”
Section: Discussionsupporting
confidence: 91%
“…When hyperglycemia is present (>160 mg/dl; >8.9 nmol/L), there is an increased competition of elevated plasma glucose with [ 18 F]FDG on carrier enzyme and, because it is usually associated with high intracellular glucose levels, also on hexokinase enzyme. As a general rule, there is a decrease in [ 18 F]FDG influx rate constant (K 1 ) quantitatively paralleling blood glucose concentrations, resulting in deterioration of image quality with increasing glucose concentrations [ 91 , 92 ]. In the case of hyperglycemia, [ 18 F]FDG uptake is expected to be reduced in the whole brain (with stochastic noise increased).…”
Section: Methodsmentioning
confidence: 99%